Site‐Selective CH Borylation of Quinolines at the C8 Position Catalyzed by a Silica‐Supported Phosphane–Iridium System. Issue 2 (4th December 2013) - Konishi, Shota; Kawamorita, Soichiro; Iwai, Tomohiro; Steel, Patrick G.; Marder, Todd B.; Sawamura, Masaya
Abstract Site‐selective CH borylation of quinoline derivatives at the C8 position has been achieved by using a heterogeneous Ir catalyst system based on a silica‐supported cage‐type monophosphane ligand SMAP. The efficient synthesis of a corticotropin‐releasing factor1 (CRF1) receptor antagonist based on a late‐stage CH borylation strategy demonstrates the utility of the C8 borylation reaction.